2017
DOI: 10.3748/wjg.v23.i27.4958
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms predict response to anti-tumor necrosis factor treatment in Crohn’s disease

Abstract: AIMTo investigate genetic factors that might help define which Crohn’s disease (CD) patients are likely to benefit from anti-tumor necrosis factor (TNF) therapy.METHODSThis was a prospective cohort study. Patients were recruited from a university digestive disease practice database. We included CD patients who received anti-TNF therapy, had available medical records (with information on treatment duration and efficacy) and who consented to participation. Patients with allergic reactions were excluded. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 42 publications
(43 reference statements)
1
36
0
Order By: Relevance
“…A combined clinical-genetic model more accurately predicted primary non-response, when compared with a clinical only model (0.93 vs. 0.70; p < 0.001) ( 23 ). Furthermore, the combination of two–risk genotypes, involving both apoptosis and the TNF region, was associated with primary anti-TNF non-response ( 93 ).…”
Section: Pharmacogenomicsmentioning
confidence: 99%
“…A combined clinical-genetic model more accurately predicted primary non-response, when compared with a clinical only model (0.93 vs. 0.70; p < 0.001) ( 23 ). Furthermore, the combination of two–risk genotypes, involving both apoptosis and the TNF region, was associated with primary anti-TNF non-response ( 93 ).…”
Section: Pharmacogenomicsmentioning
confidence: 99%
“…In fistulising CD, Fas ligand‐843 CC/CT genotype was the only predictor of response . Conversely, the CC genotype vs a TC or TT genotype was associated with primary nonresponse in CD (OR 4.3 [1.45‐12.8], P = 0.009) …”
Section: Resultsmentioning
confidence: 99%
“…Other studies found no significant association between variation in the TNF region (eg, the TNF promoter region) and treatment response . Recently however, the presence of the minor allele (A) for the TNF gene (rs1800629) was associated with primary nonresponse (OR 2.88 [1.1‐8.22], P = 0.049) …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations